Prototyping Concurrent Systems in Cw - F. Rodrigues, Nuno (2013)
Software architecture is currently recognized as one of the most critical design steps in Software Engineering. The specification of the overall system structure, on the one hand, and of the interactions patterns between its components, on the other, became a major concern for the working developer. Although a number of formalisms to express behaviour and supply the indispensable calculational power to reason about designs, are available, the task of deriving architectural designs on top of popular component platforms has remained largely informal. This paper introduces a systematic approach to derive, from behavioural specifications written in Cw, the corresponding architectural skeletons in the Microsoft .NET framework in the form of executable code